Comparative Politics of Southeast Asia An Introduction to Governments and Political Regimes - Croissant, Aurel (Springer International Publishing, 2018)
This textbook provides a comprehensive introduction to the political systems of all ASEAN countries and Timor-Leste from a comparative perspective. It investigates the political institutions, actors and processes in eleven states, covering democracies as well as autocratic regimes. Each country study includes an analysis of the current system of governance, the party and electoral system, and an assessment of the state, its legal system and administrative bodies. Students of political science and regional studies will also learn about processes of democratic transition and autocratic persistence, as well as how civil society and the media influence the political culture in each country. .